2016
DOI: 10.1111/nin.12162
|View full text |Cite
|
Sign up to set email alerts
|

“The Emperor's new clothes”: discourse analysis on how the patient is constructed in the new Swedish Patient Act

Abstract: The Swedish welfare debate increasingly focuses on market liberal notions and its healthcare perspective aims for more patient-centered care. This article examines the new Swedish Patient Act describing and analyzing how the patient is constructed in government documents. This study takes a Foucauldian discourse analysis approach following Willig's analysis guide. The act contains an entitlement discourse for patients and a requirement discourse for healthcare personnel. These two discourses are governed by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…These observations are in line with the findings of a study of discursive constructions of patients and health professionals in Sweden. The study found that in the Swedish Patient Act, New Public Management and neoliberal ideology occupied a hegemonic position (Lyckhage, Pennbrant, & Boman, 2016). In a similar vein, and arguing that there is a need for a clearer definition of the concept patient participation, a Danish study on discursive practice in mental health care (Joergensen & Praestegaard, 2017) found that patient participation was construed through a neoliberal discourse that governs underlying discourses such as legalism, rational management, and paternalism on the one hand, and ethics of care on the other.…”
mentioning
confidence: 94%
“…These observations are in line with the findings of a study of discursive constructions of patients and health professionals in Sweden. The study found that in the Swedish Patient Act, New Public Management and neoliberal ideology occupied a hegemonic position (Lyckhage, Pennbrant, & Boman, 2016). In a similar vein, and arguing that there is a need for a clearer definition of the concept patient participation, a Danish study on discursive practice in mental health care (Joergensen & Praestegaard, 2017) found that patient participation was construed through a neoliberal discourse that governs underlying discourses such as legalism, rational management, and paternalism on the one hand, and ethics of care on the other.…”
mentioning
confidence: 94%
“…Similarly, if we look at the Patient's Rights Act in Norway, this is also dominated by the discourse of expertise (Aasen & Dahl, 2019). Analysis of other similar legislations in Denmark (Lassen et al, 2018) and Sweden (Dahlborg Lyckhage et al, 2017) show that the power still belongs to the healthcare system and promotes an ideology of paternalism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Dahlborg Lyckhage, Pennbrant, and Boman (2017), Lassen, Ottesen, and Strunck (2018) and Aasen and Dahl (2019) identify ideological struggles in legal discourse across Scandinavian countries as national governance systems continue to exert hegemonic power by strongly influencing patient choice and autonomy. This mixed messaging about patient participation and autonomy in the face of NPM is evident in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…users in all parts of health care is part of a neoliberal ideology that, among others, has resulted in equalizing the differences between the public and private sectors, a policy referred to as New Public Management (Lyckhage, Pennbrant, & Boman, 2017). The discourse of applying market-based ideologies has resulted in the 'business aspect' to be more prominent, visible, for instance, in the linguistic shift from 'patient' to 'user' and in the strong focus on 'customers'' choice and rights.…”
mentioning
confidence: 99%
“…The discourse of applying market-based ideologies has resulted in the 'business aspect' to be more prominent, visible, for instance, in the linguistic shift from 'patient' to 'user' and in the strong focus on 'customers'' choice and rights. This shift is founded in arguments for increased cost efficiency and result orientation in health care, which are pursued through a strong focus on performance management, quality, and efficiency indicators (Lyckhage et al, 2017). In line with this, policy guidelines for user involvement in health services research, including nursing research, have been portrayed as crucial for a successful collaboration between users and researchers (Greenhalgh et al, 2019).…”
mentioning
confidence: 99%